A preliminary phylogenetic study of the cricket subfamily Phaloriinae (Orthoptera: Phalangopsidae: Phaloriinae) - Zhu, Yi-Ning; Hu, Tian-Hao; He, Zhu-Qing (Zootaxa, 2025)
We sequence two mitochondrial genes (COI and cytb) and two nuclear (18S and 28S) genes of 13 Phaloriinae individuals from China and Thailand. By constructing a phylogenetic tree, we found that the genus Trellius Gorochov, 1988 was not monophyletic. Thus, two subgenera Vescelotrellius and Protrellius, previously under Trellius, are upgraded as genus status.